The E16_Geometric Redesign of Road Parongpong-Ngamprah STA. 0+750-1+500 Based on Atraction-Generation Interzone Movement - Dadang Mohamad; Juang Akbardin; Odih Supratman; E. Aprian (GoAcademica Research & Publishing, 2023)
The increase in movement between zones between sub-districts in the Regency increases in line with economic development in the region. Parongpon sub-district and Ngamprah sub-district are West Bandung regency areas that have increased economic growth which is quite significant in West Bandung Regency. The geometric redesign research between Parongpong and Ngamprah zones has the aim of adjusting the road geometry based on increasing the volume generation and attraction of traffic movement between these zones. The generation and attraction of traffic movement between these zones is dominated by the volume of vehicles with larger dimensions and heavier loads, so that geometric alignment of the road is required based on the standard slope of the vertical alignment and the super-elevation curve of the horizontal alignment. The research method used is quantitative descriptive in geometric design parameters which are developed in accordance with the development of traffic volume and vehicle types. The research results show the Rise and Attract model of movement between Parongpong-Ngamprah zones with the mathematical model shown by the equation Y = 28.064 +0.0003612X1+0.001X2+0.005X3 with R2 = 0.97. With the influence of the generation of traffic volume movement on these roads, of requires adjustment of the super evaluation curve with a larger radius and smaller vertical alignment slope so that the increase in traffic volume from the influence of the generation and attraction of the movement of the Parongpong-Ngamprah zone can be anticipated with fine.